International consensus on natural orifice specimen extraction surgery (NOSES) for gastric cancer (2019). (24th January 2020) - Guan, Xu; Liu, Zheng; Parvaiz, Amjad; Longo, Antonio; Saklani, Avanish; Shafik, Ali A; Cai, Jian-Chun; Ternent, Charles; Chen, Lin; Kayaalp, Cuneyt; Sumer, Fatih; Nogueira, Fernanda; et al.
Abstract: At present, natural orifice specimen extraction surgery (NOSES) has attracted more and more attention worldwide, because of its great advantages including minimal cutaneous trauma and post-operative pain, fast post-operative recovery, short hospital stay, and positive psychological impact. However, NOSES for the treatment of gastric cancer (GC) is still in its infancy, and there is great potential to improve its theoretical system and clinical practice. Especially, several key points including oncological outcomes, bacteriological concerns, indication selection, and standardized surgical procedures are raised with this innovative technique. Therefore, it is necessary to achieve an international consensus to regulate the implementation of GC-NOSES, which is of great significance for healthy and orderly development of NOSES worldwide.